A Systematic Review on the Role of Vitamin C in Tissue Healing - Nada Bechara; Victoria M. Flood; Jenny E. Gunton (MDPI AG, 2022)
Vitamin C is an essential nutrient for humans and animals which are unable to synthesise it themselves. Vitamin C is important for tissue regeneration due to the role it plays in collagen formation, and its antioxidant properties. We reviewed the literature to evaluate potential associations between vitamin C supplementation and healing of an acute or chronic condition. Embase, Medline, PubMed, and the Cochrane Library were searched for studies published prior to April 2022. Studies were eligible if they reported at least one association between vitamin C supplementation and healing outcomes. Eighteen studies met the inclusion criteria and were included in this review. Overall, vitamin C supplementation improved healing outcomes in certain pathologies, predominantly pressure ulcers. However, many of the studies had small sample sizes, combined nutritional treatments, and did not test baseline vitamin C. Future studies should be of larger scale, exclusively using vitamin C to determine its role in tissue healing in other wounds. We recommend consideration of vitamin C supplementation for people with pressure ulcers.